Courts and Power in Latin America and Africa - Wilson, B. author. aut Link
XII, 231 p.
Keywords: Why do courts hold political power-holders accountable in some democratic and democratizing countries, but not in others? And, why do some courts remain very timid while others - under seemingly similar circumstances - become 'hyper-active'? This is valuable contribution to the ongoing debate over the issue of democratic accountability.